2002
DOI: 10.1034/j.1399-6576.2002.t01-1-460301.x
|View full text |Cite
|
Sign up to set email alerts
|

Victims of awareness

Abstract: Up to 3 weeks after their unsuccessful anesthetic, repeated information and discussions had been offered. Despite the fact that all patients at that time claimed to be satisfied with this management, and eventually considered no further contacts necessary, this was obviously inaccurate. Therefore, professional psychiatric assessment, treatment and long-term follow-up should constitute standard practice for all patients who have experienced intraoperative awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(84 citation statements)
references
References 8 publications
2
75
0
7
Order By: Relevance
“…However, the absence of early complaints does not guarantee the absence of further psychological sequelae. Lennmarken et al showed that despite the adequate early management of adults who had experienced intra-operative awareness, 44% presented important psychological sequelae two years after the event [24].…”
Section: Intra-operative Perceptionsmentioning
confidence: 99%
“…However, the absence of early complaints does not guarantee the absence of further psychological sequelae. Lennmarken et al showed that despite the adequate early management of adults who had experienced intra-operative awareness, 44% presented important psychological sequelae two years after the event [24].…”
Section: Intra-operative Perceptionsmentioning
confidence: 99%
“…Implicit and explicit recalls after procedure, resulting from too low level of anesthesia, may cause posttraumatic stress disorder (PTSD) and both acute and chronic mental disorders. These problems can affect from 4% to 70% of patients up to two years after the traumatic event 5,[7][8][9][10][11] . On the other hand, too deep a level of anesthesia can increase the incidence of postoperative cognitive decline, postoperative delirium, time of hospitalization and accelerate the onset of senile dementia [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…awareness, is evident in approximately 0.2% of cases when no neurophysiological monitoring is used to guide the conduction of anaesthesia using muscle relaxants (1). Awareness is a serious complication with a substantial likelihood of severe, long-lasting psychiatric sequelae (2). This study was designed to determine whether the introduction of routine clinical neurophysiological monitoring using the BIS A-2000 monitor (Aspect Medical Systems, Newton, MA) had any effect on the incidence of awareness.…”
mentioning
confidence: 99%